Pengembangan Media Pembelajaran Laboratorium Virtual Berbasis Discovery Learning Materi Sistem Imun Kelas XI MIPA - Risqi Irvani Wulandari; Harlita Harlita; Nurmiyati Nurmiyati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
This study aims to develop virtual laboratory learning media based on discovery learning of the immune system and to determine the feasibility of a virtual laboratory learning media based on discovery learning of the immune system. This study is a research and development adopting the 4-D device development model. In this study the design of the 4-D development was modified into 3 steps (3-D) namely Define, Design, and Develop. The study was conducted at one of the state high schools in Sragen Regency. The research subjects were divided into two, namely limited trial subjects and field trials determined using simple random sampling. The data was analized by using qualitative and quantitative techniques. The results of the study stated that virtual laboratory media based on discovery learning of immune system was created by using adobe animate CC 2017 with a design concept writing, images, animation, and video with characteristics of discovery learning models and virtual laboratory media based on discovery learning of immune system feasible to be used in learning based on validity tests from several experts with a very valid level of validity.